Dynamic structural response computation and comparison - Lim, Darren Teng Suan (Nanyang Technological University, 2024)
Modal testing is the experimental identification of the dynamic characteristics of a structure, such as its natural frequency, modal damping ratios and mode shapes. This is commonly done through techniques like the logarithmic decrement and half-power bandwidth method. Using these modal properties, the dynamic response of a structure can be predicted using the Newmark-beta method. This paper focuses on computing the dynamic response of a SDOF and MDOF structural model using a Newmark-beta algorithm, using modal properties obtained from free and forced vibration tests. The algorithm was verified analytically for an arbitrary structure, free vibration and forced vibration tests were then conducted to identify modal properties to inform the algorithm. The generated numerical response was then compared with actual forced vibration data obtained from the experiments. It was found that the frequency of the response was similar, while the amplitude of the acceleration differed slightly. Overall, for a structure of the tested scale and the magnitude of the excitation force, the algorithm gives a rough idea of the magnitude and frequency of the response, but is unsuitable if more accurate results are required.